Evidence for a neuropathic aetiology in the small pupil of diabetes mellitus. - Smith, S A (1983)
Infrared television pupillometry was performed on 34 insulin-treated diabetic patients and 55 healthy subjects. Sixteen of the diabetic patients had pupils that failed to dilate normally in darkness. The occurrence of a small pupil was associated with cardiac vagal dysfunction and somatic sensory loss. The small pupil was found to be supersensitive to the mydriatic effect of topical 2% phenylephrine but normally sensitive to 0.5% hydroxyamphetamine eyedrops. It is concluded that the failure of the pupil to dilate in darkness in some diabetic patients is due to neuropathy of the sympathetic innervation.